An overview of development and status of fiber-reinforced composites as dental and medical biomaterials - Pekka K. Vallittu (Taylor & Francis, 2025)
Fibr-reinforced composites (FRC) have been used successfully for decades in many fields of science and engineering applications. Benefits of FRCs relate to physical properties of FRCs and versatile production methods, which can be utilized. Conventional hand lamination of prefabricated FRC prepregs is utilized still most commonly in fabrication of dental FRC devices but CAD-CAM systems are to be come for use in certain production steps of dental constructions and medical FRC implants. Although metals, ceramics and particulate filler resin composites have successfully been used as dental and medical biomaterials for decades, devices made out of these materials do not meet all clinical requirements. Only little attention has been paid to FRCs as dental materials and majority of the research in dental field has been focusing on particulate filler resin composites and in medical biomaterial research to biodegradable polymers. This is paradoxical because FRCs can potentially resolve many of the problems related to traditional isotropic dental and medical materials. This overview reviews the rationale and status of using biostable glass FRC in applications from restorative and prosthetic dentistry to cranial surgery. The overview highlights also the critical material based factors and clinical requirement for the succesfull use of FRCs in dental reconstructions.